The Effect of Problem Based Learning on Students’ Ability in Writing Descriptive Text at Grade VII Students of SMP Negeri 2 Tebing Tinggi - Glean, shyndi Putri (Pascasarjana Universitas HKBP Nommensen, 2022)
This research is the study of teaching students’ ability in writing descriptive text at grade seven in SMPNegeri 2 Tebing Tigggi. It deal with the Problem Based Learning (PBL) method in teaching writingdescriptive text at grade VII of SMP Negeri 2 Tebing Tinggi”. The researcher uses some theories tocomplete this thesis, they were: Heaton (1981), Indonesian Educational Department (2013), Keraf(2000), Kane (2002), Dutch (1995). This research, Uses experimental design which consist of post-testto know the effect of using PBL on students’ writing ability. The sample divided into 2 groups. They areexperimental group and control group. In this research there were 60 students divided into two classes.Every group had 30 students in experimental group and 30 students in control group. After the data hadbeen analyzed, the Alternative hypothesis (Ha) is accepted and Null hypothesis (Ho) is rejected. It showsthat t-obtained value is higher than t-table (2.68>1.67). It means that PBL more significant affect on thestudents’ ability in writing descriptive text than without using PBL. Consequently the researchersuggests PBL method to the teacher in learning process especially in teaching writing descriptive text,because PBL is one of teaching method that make the students easier to write a text.